(3JaSjQ ShQI (B" (3bd gh Gddg CMO hGdeYhPJjf(B"s - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bd gh Gddg CMO gh GdeWdb s
(3BNQgG (B:s
(3bGd Gddg ef GdLfI hGdfGS hgPG gh GdPi HdZ GdYbd Edjg ai gPg GdShQI hGddg GYde HGdUhGH hZdjg GdeQLY hGdeGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B403 - (3U(B407s
(3GfXQg eY GdeNWhW Qbe (B292s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(38 / 1035) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs